Mobile sensing system for cycling power output control - Afonso, José A. (2017)
This paper describes the development of a novel cycling effort control sys-tem that contributes to promote the users’ physical health and mobility. This system controls the motor assistance level of an electric bicycle in order to ensure that the cyclist’s power output remains inside the desired limits, regardless of changes in variables such as the speed of the bicycle or the slope of the terrain. The power output is monitored using a sensor device that provides raw torque and cadence data, whereas a smartphone application processes these data, implements the effort control algorithm and provides the user interface. Modules on the bicycle handle the data acquisition, wire-less communication with the smartphone and driving of the motor assis-tance level. Experimental results validate the effectiveness of the imple-mented power output control system.